Optimizing Arowana Fish Breeding with IoT Aquaculture - Agus; Suryadiputra Liawatimena; Gilang Wiranda; Diki Arisandi (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2024)
Monitoring and controlling water temperature and pH levels are crucial aspects in maintaining a healthy environment for breeding Arowana fish. Arowana fish are sensitive to fluctuations in water temperature and pH levels, which can lead to stress, diseases, and even death. Therefore, it is essential to regularly monitor and maintain the temperature and pH levels within suitable ranges for the fish. This study aims to develop Internet of Things (IoT) technology that is expected to assist Arowana fish farmers in monitoring and controlling more effectively and practically. The methodology employed in this study is a case study approach, with Arowana fish farmers as respondents. In monitoring the water quality for Arowana fish, many farmers still rely on traditional farming models that heavily depend on experience, lacking the ability to assess water quality and environmental changes scientifically. By utilizing LoRa and cellular technologies, this study provides intelligent solutions for water quality monitoring to create controlled and sustainable growth conditions. The ultimate outcome of this research is the development of an IoT-based application designed to enhance the efficiency of Arowana fish farming. This application involves automatic control of water pH and temperature in three different treatments. The methodology employed in the application design involves the development of an IoT-based system integrated with temperature and pH sensors. The functionality of the application includes real-time monitoring and automatic control of the aquarium environment. Testing was conducted through a series of field trials to ensure system performance and reliability. With a pH range of 6.5 - 7.5 and temperature range of 26 - 30°C, this application has proven to provide optimal responses for Arowana fish farming, enhancing growth and reducing feeding time.